Background Notes (Washington, DC U.S. Government Printing Office, 2006)
Background notes are short, authoritative pamphlets about various countries, territories, international organizations, written by officers in the Department Office of Public Communications, Bureau of Public affairs.
Included is map, a bibliography, and a travel-notes section
300148
Keywords: Geography; Government; History